Implementasi Penerapan Program Keselamatan dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan PT. Retota Sakti Kota Pekalongan Di Era New Normal - Aria Mulyapradana; Yustiana Dwirainaningsih; Salman Al Farisi (Universitas Bina Sarana Informatika, 2022)
AbstractThe purpose of this research is to determine the effect of implementing safety and health programs on work productivity in the new normal era at PT. Retota Sakti Pekalongan City. This research uses quantitative methods and explanatory research and the number of respondents is 90 respondents who are employees of PT. Retota Sakti. Occupational safety and health of employees is one of the determining factors for the success of companies both engaged in the production of goods and services. Productivity itself is not new in the business world, so many opinions or business perspectives are raised, how to actually measure the productivity standards of a business or company. So how much attention the company pays to the safety and health of employees in increasing their productivity. In the new normal era, it seems that it is now one of the words that are often echoed by business people. Not because the new normal era is a transition period from the COVID-19 pandemic, but precisely because the new normal era was the beginning of the revival of the productivity of business people since previously being shackled in the Covid-19 circle. This research concludes that there is an effect of work safety on work productivity and the effect of occupational health on work productivity in the new normal era. Keywords: work safety, occupational health, work productivity, new normal, covid-19